Expression of annexin A5 in serum and tumor tissue of patients with colon cancer and its clinical significance - Sun, Chong-Bing (World J Gastroenterol, 2017)
AIM: To investigate the expression of annexin A5 in serum and tumor tissue of patients with colon cancer and to analyze its clinical significance. METHODS: Ninety-three patients with colon cancer treated at our hospital between February 2013 and March 2016 were included in an observation group, and 40 healthy individuals were included in a control group. Enzyme-linked immunosorbent assay was performed to determine the serum level of annexin A5, while immunohistochemistry was performed to determine the expression of annexin A5 in cancer tissues. RESULTS: The serum level of annexin A5 was 0.184 ± 0.043 ng/mL in the observation group, which was significantly higher than that in the control group (P < 0.05). Annexin A5 expression was detected in 79.31% of the patients with lymph node metastasis, which was significantly higher than that in patients without lymph node metastasis (P < 0.05). Moreover, annexin A5 expression was detected in 86.96% of the patients with stage III to IV disease, which was significantly higher than that in patients with stage I to II disease (P < 0.05). The serum level of annexin A5 was 0.215 ± 0.044 ng/mL in patients whose tumors were positive for annexin A5 expression, which was significantly higher than that in patients whose tumors were negative for annexin A5 expression (P < 0.05). The serum level of annexin A5 was correlated with annexin A5 expression in colon cancer tissues (r = 0.312, P < 0.05). When a cutoff value of > 0.148 ng/mL for serum level of annexin A5 was used in the diagnosis of colon cancer, the sensitivity was 83.90%, and the specificity was 57.50%. CONCLUSION: For patients with colon cancer, annexin A5 expression in cancer tissues is related to lymph node metastasis and tumor grade. Serum level of annexin A5 is related to annexin A5 expression in cancer tissues and is of diagnostic relevance.